The issue of recognition of ecocide as a crime by environmental courts and tribunals - Tulibayev, S.T. (Bulletin of the Karaganda University “Law Series”, 2024)
The article analyzes the recognition of ecocide as a crime by judicial institutions. Ecocide still has not re-ceived a well recognized definition. However, the proposal to acknowledge ecocide as an international crime developed by the Independent Expert Panel for the Legal Definition of Ecocide, as well as the recognition of environmental crimes similar to ecocide as set out in the Proposal for a Directive of the European Parliament and of the Council on the protection of the environment through criminal law, should be highlighted and ana-lyzed. The purpose of the study is to analyze the impact of new approaches to the crime of ecocide on the practice of environmental courts and tribunals. By the application of general and specialized research meth-ods, the author identifies possible changes in the jurisprudence of already existing judicial institutions, as well as the likelihood of the emergence of international courts and tribunals dedicated to separate cases of ecocide. The article concludes that new approaches to the definition of ecocide may lead to further development of in-ternational environmental law and national environmental law of the Republic of Kazakhstan, as well as the possible emergence of effective international mechanisms to protect international environmental security.